PENGARUH INFLASI, SUKU BUNGA SBI, KURS US DOLLAR TERHADAP RUPIAH, PAJAK, SOLVABILITAS, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2015 - Budiono Budiono; Nur Septiani (BISMA (Bisnis dan Manajemen), 2018)
The capital structure is the ratio between long-term debt and equity capital used by the company. By using a proper comparison it will obtain an optimal capital structure. Optimal capital structure is capital structure which optimizes the balance between risk and return in order to maximize the stock price. The purpose of this study was to determine the factors that affect the company's capital structure of LQ-45 listed on the Indonesia Stock Exchange 2010-2015 period. The sampling technique used is purposive sampling method that produces as many as 13 companies. The analysis technique used is multiple linear regression. The results showed that all independent variables simultaneously affect the capital structure. T test results showed that the variable of exchange rate of US dollar against the rupiah has significant negative effect on the capital structure, the variable of tax has positive and significant impact on the capital structure, the variable of solvency has positive and significant impact on the capital structure and profitability variable has significant negative effect on the capital structure. While the variable inflation and SBI interest rate has no significant effect on the capital structure.